Eksistensi Prinsip Responsibility to Protect Dalam Hukum Internasional - Rahayu Rahayu (Faculty of Law, Universitas Diponegoro, 2012)
The responsibility to protect (R to P or R2P) is a norm or set of principles based on the idea that sovereignty is not a privilege, but a responsibility. R to P concept focuses on the three pillars. These are : the responsibility of each individual state to protect its population from genocide, war crimes, ethnic cleansing, and crimes against humanity and their incitement; the responsibility of the international community to undertake peaceful collective action to help states to exercise this responsibility; and the responsibility of the international community to be prepared to take collective action in a timely and decisive manner through the UN Security Council. Any form of a military intervention initiated under the premise of responsibility to protect must fulfill the following six criteria in order to be justified as an extraordinary measure of intervention : just cause, right intention, final resort, legitimate authority, proportional means and reasonable prospect.Keywords : Responsibility to protect, international community